Maternal behavior as an early modulator of neurobehavioral offspring responses by Sprague-Dawley rats - Sequeira Cordero, Andrey (2013)
Maternal care plays an important role as an early modeler of neurodevelopment and brain function, and its effects remain until adulthood. Such modeling or programming has shown to influence the stress response and represents a key susceptibility factor in the development of mood disorders. In order to characterize such process which is still not clear, male offspring were classified in animals with low, medium and high licking/grooming (LG) according to the maternal behavior. Juvenile animals were subjected to the open field test (OFT) and the forced swimming test (FST), and offspring of low and high LG mothers were compared. Seven days after the FST, neurochemical and gene expression analyses were carried out in order to identify possible changes on relevant targets. Maternal care did determine locomotor behaviors in the OFT, supporting an anxiogenic effect of low maternal investment. This effect seems to be associated with the serotonergic systems in both nucleus accumbens (NAc) and hippocampus (HPC), since offspring of low LG mothers showed decreased 5-HT neurotransmission in those brain regions compared with animals of high LG mothers. Furthermore, TrkB expression was higher in offspring of high LG compared to the group of low LG mothers, supporting its influence as a mechanistic intermediate of such effect, at least in the NAc. Taken together, these findings strongly support the influence of differential maternal care on the neurodevelopment and responsivity of juvenile rats